From Global to Local in the Sneakers Universe: A Data Science Approach - Perdomo, Luciano (2021)
In Argentina there was a great growth of e-commerce due to the COVID-19 pandemic. With the aim of helping local companies to understand the market and help them in decision making, data were obtained from online shoe sales sites and with them Machine Learning models were implemented to make price predictions in sneakers. It was concluded that higher-tier companies have greater competitive advantage over lower-tier companies. Nonetheless, the cost-effective methodology used would aid local companies scale up.